Ln-type estimators for the estimation of the population mean of a sensitive study variable using auxiliary information - Muhammad Nouman Qureshi; Yousaf Faizan; Amrutha Shetty; Marwan H. Ahelali; Muhammad Hanif; Osama Abdulaziz Alamri (Heliyon, 2024)
In this article, we offered two ln-type estimators for the population mean estimation of a sensitive study variable by using the auxiliary information under the design of basic probability sampling. The Taylor and log series were used to derive the expressions of mean square error and bias up to the first order. Improved classes of proposed estimators are obtained by using conventional parameters associated with the supplementary variable to obtained precise estimates. Mathematical comparisons of the estimators have been made with the usual mean and ratio estimators using theoretical equations of mean square error. A simulation study is conducted for the evaluation of proposed estimator's implementation using four artificial populations generated through R-software with different choices of mean vectors and variance-covariance matrices. The demonstration of proposed ln-type estimators was implemented through the real data application.